Pembelajaran Kitab Mabadi Fiqih untuk Meningkatkan Belajar Bersuci di Era Pandemi Covid-19 Anak Desa Butuh – Kras – Kediri - Lailatul Munawaroh; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
In essence, learning is a process of interaction between teachers and students, both direct interactions such as face-to-face activities and indirectly, namely by using various learning patterns. Autonomy in the field of education has given opportunities and authority to every educational institution to make various innovations in developing and implementing curriculum and learning. That way every educational institution has one uniqueness that is highlighted in developing its institution. This uniqueness can be highlighted with learning programs or others. In the study itself the author chose to use the PAR (Participatory Action Research) method, The PAR method is one of the research models that looks for something to connect the research process into the process of social change. By directly participating in accompanying children by using the media of the book Mabadi Fiqh is expected to increase their knowledge through learning to purify properly remember their knowledge about this is classified as lacking.